Portable system for monitoring and recording multivariate workplace environmental variables in hydroelectric power plants - Andreoli, Andre Luiz [UNESP]; Franchin, Marcelo Nicoletti [UNESP]; Cagnon, Jose Angelo [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2014)
This paper presents research and development results of a prototype portable system designed for monitoring and recording HPP (Hydroelectric Power Plant) workplace environment data (noise, vibration, pressure, temperature, gas concentration and light level), related to working health conditions observing the requirements from current national and international standards. This has been achieved by using a series of dedicated sensors connected via wireless network to a portable intelligent computing platform in order to diagnosis the risks which workers are subjected to and also for improving the quality of life at work. The main contributions of this work are highlighted by technological innovation in state of the art of hardware and software components used (sensors, microcontrollers, computer, operating system, etc.), simultaneous multivariate acquisition and recording of environment workplace data, a novel methodology able to measure, record, analyze and diagnose risks, automatic generation of technical reports and risk maps, and creation of an innovative database for planning and following preventive and corrective maintenance actions over workplace conditions. The final product may be used by any company of electricity generation, especially HPP. Furthermore, this system will be of great value to the whole electric power industry, particularly power generation, as it will allow an integrated real-Time and continuous monitoring of occupational risks, helping work-related injury and illness preventive actions as a permanent preventive occupational safety and health program, thus resulting in an increasing of quality and reliability aimed for excellence. The research and development prototype was successfully designed, produced and tested through P&D funding from a HPP company at Sao Paulo.